Digital Resilience of the Bucharest Nine and Ukraine - Shkuropadska, Diana; Tokar, Volodymyr; Purdenko, Olena; Lotariev, Andrii; Savchuk, Kyrylo (International Journal of Economics and Financial Issues, 2024)
This study examines the digital resilience of the Bucharest Nine, an Eastern European NATO alliance, and Ukraine amidst the challenges of digital transformation. It aims to identify factors influencing their ability to manage cyber threats, digital divides, and socio-economic disparities resulting from rapid digitalization. Using a mixed-methods approach, integrating quantitative analysis and qualitative insights, the research computes an index of digital resilience based on cybersecurity measures, digital infrastructure quality, and socio-economic impacts. Findings reveal varying resilience levels, with some countries demonstrating robust cyber defenses and advanced digital infrastructures, while others lag due to weaker capacities and socio-economic constraints. Comprehensive policy frameworks and inclusive digital strategies are emphasized as critical for enhancing resilience. However, the study’s focus on the Bucharest Nine and Ukraine may limit broader regional representation, and reliance on available data and potential biases in self-reported indices may affect comprehensiveness. Nonetheless, the insights can inform policymakers in developing targeted strategies to bolster digital resilience, emphasizing cybersecurity, bridging the digital divide, and promoting digital literacy and participation. This research contributes to understanding digital resilience by offering a comparative analysis of often overlooked geopolitical regions, combining various indicators to provide a holistic view of their digital landscapes.